the role of the teacher in the effectiveness of student learning in inclusive schools at SD N 53 Banda Aceh City. - reza, nofria; soedirman, Soedirman; Israwati, Israwati (Universitas Syiah Kuala, 2023)
An inclusive school is a school that accepts students with the limitations of a student and normal students in the same school environment. Therefore the teacher will have an additional role in the classroom where in inclusive schools mix children with special needs with regular children in one class. Researchers are trying to reveal part of the teacher's role in SD N 53 Kota Banda Aceh and whether this inclusive school is running effectively. This study uses a qualitative approach and descriptive research type. The research subjects were 4 teachers and one class observation. Data collection techniques using observation and interviews. Data were analyzed by data reduction, data presentation, and drawing conclusions. The results of this study indicate that the teacher's roles have been fulfilled and carried out properly in accordance with the following 9 indicators of the teacher's role: (1) educator, (2) teacher, (3) facilitator, (4) mentor, (5) servant, ( 6) Designers, (7) Managers, (8) Innovators, and (9) Assessors. Then this inclusive school is considered to have been running effectively based on the description of the following indicators of learning effectiveness: (1) organizing and planning learning; (2) good communication; (3) mastery and enthusiasm for learning materials; (4) flexibility in approach; (5) giving a fair value; (6) good participant learning outcomes.